TOLERANSI PERSPEKTIF HAMKA DALAM TAFSIR AL-AZHAR - Eduwar; Nurbaiti; Khaulah Nabila Amjad (Universitas PTIQ Jakarta, 2023)
The aim of this research is to explain tolerance from Hamka's perspective which the author found in Tafsir Al-Azhar. This paper finds the principles of tolerance in Hamka's Tafsir Al-Azhar. Tafsir Al-Azhar is a commentary on Hamka's work which focuses more on the adâbi ijtimâ'i interpretation style. This can be seen in the explanation in Tafsir Al-Azhar regarding the principles of tolerance, such as: Compassion and good behavior between religious communities (Q.S. al-Fâtihah/1: 1), freedom of religion (Q.S. al-Baqarah/2: 256; al-Kahfi/18: 29), Enable tolerance amidst diversity, (Q.S. al-Hujurât/49: 13, Mutual respect between religious communities, (Q.S. al-Baqarah/2: 62). This research uses an approach literature (library research). The research method used in this scientific work is qualitative research methods. The conclusion in this research is that tolerance Hamka in Tafsir Al-Azhar promotes the paradigm of tolerance between religious communities, that in social life there are various kinds of differences such as ethnicity, race, language, culture, customs and also religion. With an attitude of tolerance, a person can invite peace towards other religions and give freedom to followers of certain religions in choosing a religion according to their respective beliefs without any coercion